Lack of clinical disease activity response at 4 weeks of baricitinib treatment as a negative predictor of remission at weeks 12 and 24 in patients with rheumatoid arthritis: results from two phase 3 studies (RA-BEAM and RA-BEGIN) - Tanaka, Y; Weinblatt, M; Taylor, PC; Fleischmann, R; Ishizuka, T; Tanaka, M; Takita, Y; Schlichting, D; Takeuchi, T (Iyaku-Joho-Kenkyujo, Inc., 2021)
Objective: To determine whether early changes in disease activity predict later achievement of low disease activity (LDA) or remission in patients treated with baricitinib 4 mg in global phase 3 studies.